Основные особенности школы «черного юмора» и творчество Томаса Пинчона - Алиева, Х.Э. (Культура народов Причерноморья, 2014)
В статье анализируется творчество одного из основных представителей постмодернистской литературы СА и школы «черного юмора» Томаса Пинчона. Здесь рассмотрены его место и роль в развитии литературы постмодернизма, мистификация, присутствующая в авторской позиции писателя. На основе произведений Пинчона к анализу также были привлечены характерные черты школы «черного юмора». В статье отражается анализ его произведений, особенно таких романов как «V.», «Выкрикивается лот 49», «Радуга земного тяготения» и включены в данное исследование. У статті аналізується творчість одного з основних представників постмодерністської літератури СА й школи «чорного гумору» Томаса Пінчона. Тут розглянуто його місце та роль у розвитку літератури постмодернізму, містифікації, які присутні у авторської позиції списателя. На основі творів Пінчона до аналізу також були залучені характерні риси школи «чорного гумору». У статті відображається аналіз його творів, особливо таких романів, як «V.», «Вигукується лот 49», «Веселка земного тяжіння» та включні в дане дослідження. The article deals with the investigation of Thomas Pynchon’s creative work, which is one of the main representatives of postmodern literature and school of black humor of the USA. Here is investigated his place and role in the development of postmodern literature, and here is told about his mystification in the author’s position. The research of the features of specifications of the school of black humor, characteristics of the author’s creative work and his works are also reflected in the article. His works, especially the novels as the “V.”, “The Crying of Lot 49”, “Gravity’s Rainbow” is reflected in the article and they have been included in the investigation. The way that Thomas Pynchon took place in the world literature with his novel “V.” was mentioned in the article. His genius showed itself clearly in this work. So that, within each chapter of the novel we meet the chronology of historical events of the twentieth century. The meaning of the article V. was opened and the novel has been widely analyzed in the investigation. Thomas Pynchon’s second novel “The Crying of Lot 49” also has been analyzed here. The emphasis of the element of paranoia, which is used as a means of communication within the community, is reflected to the analysis in this article. In analyzing the novel “Gravity’s Rainbow” it is shown that the novel is based on the manipulation of the human psyche. So, an investigation of main features of the school of black humor and Thomas Pynchon’s creative activity that is coherent with this school are reflected in the article